Indoor air pollutants produced from fossil fuel and biomass - Lodhi, M.A.K.; Zain-al-Abdin, A. (Elsevier, 1999)
The major source of indoor air pollutants, such as suspended particle matter (SPM) and carbon monoxide (CO), is the smoke emission from the use of domestic energy for cooking and heating. The exposure of rural housewives to SPM and CO was monitored for 10 weeks during their cooking activities. The levels of pollutants, especially from burning firewood, were found to be high but not to a hazardous degree. The situation can turn for the worse, if no deliberate effort is made to improve the conditions of the households using firewood. In fact, both gas and firewood should be replaced by some other clean energy fuels obtainable from renewable energy sources. © 1998 Elsevier Science Ltd. All rights reserved.